A novel L-β-Galactoglucan alleviates physical fatigue by modulating load-specific metabolic pathways via the gut–muscle Axis - Jun He; Lingling Du; Meng Wang; Yurui Gou; Ziqi Xu; Shubin Yan; Yimiao Feng; Xiaohua Lyu; Jinyao Chen; Lishi Zhang; Xiaomeng Li (Food Research International, 2026)

Root trait responses of Ligustrum lucidum to edaphic stress across limestone and sandy shale areas - Yurui Cheng; Yongjun Jiang; Mengni Li; Jiabin Li; Fang Liu; Peiling Zhang; Qiufang He (Plant and Soil, 2025)

Genotoxicity mode of action exploration of polyethylene glycol terephthalate (PET) acetic acid migration solution under repeated-dose exposure in rats - Liang Wang; Li Cao; Xiaoya Wang; Yufei Liu; Weiwei Zhang; Yurui Gou; Jun He; Jiao Huo; Xiaomeng Li; Jinyao Chen (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2025)

Significantly enhanced piezoelectric properties of BaTiO3-based ceramics with unchanged curie temperature via local chemical inhomogeneity - Ming Wu; Ruifeng Yao; Chengyichang Jin; Yurui Xu; Jingzhe Xu; Liqiang He; Yang Yang; Yongbin Liu; Lisheng Zhong; Jinghui Gao (Chemical Engineering Journal, 2025)

A flexible, highly sensitive, and anti-strain interference sensing fabric based on conjugated electrospinning core–shell conductive nanofiber yarns for ultra-stable pressure sensing and human–machine interaction - Wenqi Wu; Xu Jin; Adilaimu Tiliman; Fan Zhang; Ge Bai; Yurui He; Gaoling Jin; Bin Wang; Xiuqin Zhang; Rui Wang (Chemical Engineering Journal, 2025)

Experimental study on environmental chemical effect and purification treatment of waste slurry in horizontal directional drilling - Pinghe Sun; YuRui He; Shengwei Zhou; Habiyakare Erneste; Qiang Gao; Zihao Zou; Junyi Zhu (Tunnelling and Underground Space Technology, 2024)

Regularity of rural settlement changes driven by rapid urbanization in North China over the three decades - Yansui Liu; Cong Ou; Yurui Li; Liqiang Zhang; Jianhua He (Science Bulletin, 2023)

Occupant-centric dynamic heating and cooling loads simplified prediction model for urban community at energy planning stage - Shuqin Chen; Yurui Huang; Xiyong Zhang; Frédéric Kuznik; Xi He; Yuhang Ma; Yuxuan Cai (Sustainable Cities and Society, 2023)

Research on non-contact wet mateable connector for optical communication and power transmission - Zhiyong Duan; Yurui Zhang; Jiaqi Hu; Bohao He; Canjun Yang (Frontiers in Marine Science, 2023)
At present, contact watertight connectors are commonly utilized for the connection between underwater electromechanical equipment and the seabed observation network. Such traditional watertight connectors are easy to be irreversibly worn when plugging and unplugging, however, they have complicated sealing structures and limited service life. This paper designs a Non-contact Wet Mateable connector for Optical Communication and Power Transmission (OCPT-NWMC), which is based on technology of Contactless Power Transmission (CLPT) and optical communication. Docking structure of the sockets and plugs are designed, facilitating Remotely Operated Vehicle (ROV) to operate. A prototype of the OCPT-NWMC was established. The experimental results show that the connector designed can achieve 200W power transmission, with a maximum power transmission efficiency of 94%. The communication bandwidth reaches 18MHz. The OCPT-NWMC can assist the rapid and safe deployment and operation of seabed observation network.